2016
DOI: 10.2214/ajr.15.15462
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Tumor Quantitative Apparent Diffusion Coefficient Histogram and Texture Analysis to Predict Gleason Score Upgrading in Intermediate-Risk 3 + 4 = 7 Prostate Cancer

Abstract: In this study, whole-lesion mean ADC, ADC ratio, and ADC histogram analysis were not predictive of pathologic upgrading of GS 3 + 4 = 7 prostate cancer after RP. ADC texture analysis improved accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…However, on final pathology, five of 13 patients (38.5 %) were upgraded. These rates of upgrading appear consistent with prior reports in HIV-negative populations [19]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, on final pathology, five of 13 patients (38.5 %) were upgraded. These rates of upgrading appear consistent with prior reports in HIV-negative populations [19]. …”
Section: Discussionsupporting
confidence: 92%
“…HIV-positive patients were more likely to be African-American (53.8 vs. 19.3 %, p = 0.005) ( Table 1).…”
Section: Patient Population and Baseline Characteristicsmentioning
confidence: 99%
“…To our knowledge, there is no study in the literature that has specifically evaluated texture analysis in prostate cancer for diagnosis of EPE. Previous studies by Rosenkrantz et al and Wibmer et al demonstrated that ADC entropy correlated with Gleason score, and in a study by Rozenberg et al texture analysis modeling could predict Gleason 3 + 4=7 upgrading after RP. These preliminary results, combined with our own data, suggest that there is a role for texture analysis of prostate cancer for determining disease aggressiveness.…”
Section: Discussionmentioning
confidence: 91%
“…Three parameters were studied: kurtosis (a measure of histogram flatness), skewness (a measure of histogram asymmetry), and entropy (a measure of histogram irregularity) using an in‐house software plug‐in for ImageJ. ADC and first‐order texture features were selected for analysis, as these have been best studied previously …”
Section: Methodsmentioning
confidence: 99%
“…13 Diffusion tensor imaging, based on DWI technique, can reflect the diffusion rate and direction of water molecules, 14 with ADC T value and FA value, respectively. 15 Apparent diffusion coefficient and ADC T value are positively related with water molecule movement speed.…”
Section: Discussionmentioning
confidence: 99%